ANALYSIS OF WEBSITE QUALITY OF SISFO UNIVERSITY OF PGRI PALEMBANG USING WEBQUAL 4.O - Ramdani Anjas Stiawan; Iin Seprina (Institute of Computer Science (IOCS), 2022)
User satisfaction of a system is a measure of the success of the system. With information technology, universities can easily disseminate information to students lecturers and staff. Therefore, the ease and accruracy of information technology in universities is very necessary. The website is a complete information provider and has become one of the important aspects in various fields, especially education because it can be accessed easily and without restrictions. In this study, the quality of the Sisfo website of PGRI Palembang was measured using the Webqual 4.0 method. The source of this research data was obtained from processed quastionnaires from the faculty of teacher tarining and education at the University of PGRI Palembang 2018 batch with a population of 5363 and a sample of 372 respondents. The results of the study can be said that simultaneously the quality of the website affects the quality of the website. While partially one of the dimensions of webqual, namely usability, does not significantly affect the quality of the website. In other words, the usability dimension must be improved again.